Evaluating historic and modern optical techniques for monitoring phytoplankton biomass in the Atlantic Ocean - Brewin, Robert J. W.; Pitarch, Jaime; Dall’Olmo, Giorgio; van der Woerd, Hendrik J.; Lin, Junfang; Sun, Xuerong; Tilstone, Gavin H. (Frontiers in Marine Science, 2023)
Traditional measurements of the Secchi depth (zSD) and Forel-Ule colour were collected alongside modern radiometric measurements of ocean clarity and colour, and in-situ measurements of chlorophyll-a concentration (Chl-a), on four Atlantic Meridional Transect (AMT) cruises. The data were used to evaluate historic and modern optical techniques used for monitoring Chl-a, and to evaluate remote-sensing algorithms. Comparisons between historic and modern optical measurements were broadly consistent with current understanding, with Secchi depth inversely related to Forel-Ule colour and to beam and diffuse attenuation, positively related to the ratio of blue to green remote-sensing reflectance and euphotic depth. The relationship between Secchi depth and Forel-Ule on AMT was found to be in closer agreement to historical relationships when using data of the Forel-Ule colour of infinite depth, rather than the Forel-Ule colour of the water above the Secchi disk at half zSD. Over the range of 0.03-2.95 mg m-3, Chl-a was tightly correlated with these optical variables, with the ratio of blue to green remote-sensing reflectance explaining the highest amount of variance in Chl-a (89 %), followed by the Secchi depth (85 %) and Forel-Ule colour (71-81 %, depending on the scale used). Existing algorithms that predict Chl-a from these variables were evaluated, and found to perform well, albeit with some systematic differences. Remote sensing algorithms of Secchi depth were in good agreement with in-situ data over the range of values collected (8.5 - 51.8 m, r2 > 0.77, unbiased root mean square differences around 4.5 m), but with a slight positive bias (2.0 - 5.4 m). Remote sensing algorithms of Forel-Ule agreed well with Forel-Ule colour data of infinite water (r2 > 0.68, mean differences <1). We investigated the impact of environmental conditions and found wind speed to impact the estimation of zSD, and propose a path forward to include the effect of wind in current Secchi depth theory. We discuss the benefits and challenges of collecting measurements of the Secchi depth and Forel-Ule colour and propose future directions for research. Our dataset is made publicly available to support the research community working on the topic.